(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The deployment of fifth-generation (5G) cellular networks demands advanced antenna systems capable of delivering high gain, wide bandwidth, low return loss, and efficient beamforming. This article presents a comprehensive comparative analysis of wired antenna arrays specifically dipole arrays, Yagi-Uda arrays, and log-periodic dipole arrays (LPDAs) designed for 5G base station applications at 3.5 GHz. Using CST Microwave Studio simulations, single-element and multi-element configurations were evaluated against key performance metrics including return loss, VSWR, gain, directivity, bandwidth, and radiation pattern characteristics. The ten-element dipole array achieved a gain of 11.79 dBi with a narrow beamwidth of 16.4°, representing a 9.5 dB improvement over a single dipole. The ten-director Yagi-Uda demonstrated superior return loss (-25.22 dB) and gain (11.7 dBi) compared to the three-director version (8.9 dBi). The four-element LPDA array exhibited enhanced bandwidth (0.508 GHz) and improved VSWR (1.255) relative to its single-element counterpart. These findings provide quantitative guidelines for selecting optimal wired antenna configurations for specific 5G deployment scenarios.